2020
DOI: 10.3390/microorganisms8101544
|View full text |Cite
|
Sign up to set email alerts
|

Culturomics Discloses Anti-Tubercular Enterococci Exclusive of Pulmonary Tuberculosis: A Preliminary Report

Abstract: Mycobacterium tuberculosis causes pulmonary tuberculosis, a deadly infection of which the clinical expression and prognosis are not fully understood at the individual level, apart from genetic susceptibility traits. We investigated whether individual gut microbiota may correlate with pulmonary tuberculosis status. Culturomics investigations of gut microbiota in two pulmonary tuberculosis patients and two controls in Burkina Faso found 60 different bacterial species in patients and 97 in controls, including 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
2
3
1
Order By: Relevance
“…The fact that E. mundtii inhibited the growth of some MTC species had been previously described in our laboratory [23], and the data reported here broadened such previous observations by cross-incorporating a set of E. mundtii strains and MTC species using a standardized agar well diffusion assay to compare cross-inhibition values. Accordingly, we observed that both E. mundtii suspensions and derived lyophilized culture supernatants inhibited the growth of M. tuberculosis, M. africanum, M. bovis and M. canettii.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The fact that E. mundtii inhibited the growth of some MTC species had been previously described in our laboratory [23], and the data reported here broadened such previous observations by cross-incorporating a set of E. mundtii strains and MTC species using a standardized agar well diffusion assay to compare cross-inhibition values. Accordingly, we observed that both E. mundtii suspensions and derived lyophilized culture supernatants inhibited the growth of M. tuberculosis, M. africanum, M. bovis and M. canettii.…”
Section: Discussionsupporting
confidence: 82%
“…The fact that E. mundtii inhibited the growth of some MTC species had been previously described in our laboratory [23], and the data reported here broadened such previous observations by cross-incorporating a set of E. mundtii strains and MTC species using a standardized agar well diffusion assay to compare cross-inhibition values.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…As reported in our previous work ( 23 ), lactobacilli from the TB-free estates (group 1) significantly inhibited M. bovis BCG, probably through the combination of multiple synergistic metabolites such as organic acids, hydrogen peroxide, ethanol, and unmodified two-peptide bacteriocins. Enterococci from the TB estates (group 2) showed a much lower reduction of BCG survival, which contradicts some authors who demonstrated the antimycobacterial effect of enterococci ( 57 ). Strikingly, the P. acidilactici strain (C5) from the TB-free group showed a much higher antimycobacterial activity than that of the P. acidilactici strain (R91) isolated from the estate with a high TB prevalence.…”
Section: Discussioncontrasting
confidence: 63%
“…Significant alterations have been observed in the gut microbiota composition of PTB patients compared to healthy individuals ( Hu et al, 2019 ). In Burkina Faso, the growth of M. tuberculosis strains in vitro was found to be inhibited by two Firmicutes species, namely E. casseliflavus and E. mundtii , which were isolated from patients who tested negative for TB ( Fellag et al, 2020 ). A study conducted in western China revealed a direct relationship between the gut microbiota and the number of peripheral CD4 + T cells in individuals with tuberculosis ( Luo et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%